The Grit and Grist of Thinking… - Ben Nicholson (Oz, 1993)
Wandering Leaves. It was a weekend of trees in October. There are so many trees in Pennsylvania that they appear to have run amok. The trees are shedding leaves to such an extent that they have gone out of control. Ed. note: See related article, "...The Unthinkable House."